KEMAMPUAN TRANSLASI REPRESENTASI MATEMATIS SISWA PADA MATERI PENJUMLAHAN PECAHAN DI SMP MUHAMMADIYAH 2 PONTIANAK - Dian Arifyati; Halini Halini; Dede Suratman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research aims to determine and describe the translation ability of students' mathematical representations in the material of adding fractions in class VII SMP Muhammadiyah 2 Pontianak. The subjects of this study were 27 grade VII students of SMP Muhammadiyah 2 Pontianak. The method used in this research is descriptive method with a survey form. The techniques used in this research are measurement techniques through written tests in the form of essays and direct communication techniques through interviews. Based on the results of data analysis, the translation ability of students' mathematical representations is included in the medium category. The ability to translate students 'representations from verbal to symbolic forms is in the high and very high category and vice versa, the translational ability of students' representations from symbolic to verbal forms is in the low, medium and high categories. The ability to translate students 'representations from verbal to image forms is in the medium, high and very high categories and vice versa, the translational ability of students' representations from images to verbal forms is in the medium, high and very high categories.Keywords: Fraction, Representation, Translation Ability